Analisis Startegi Kreatif Iklan Marjan 2024 “Putri Hijau Dan Desa Kehidupan" - Dhea Arien Febrianie; Hestia Rachmat Nunciata Lubis; Echa Nabila (VisArt: Jurnal Seni Rupa dan Design, 2026)
This study aims to analyze the creative strategy of using storytelling through Indonesian traditional and cultural narratives with a cinematic concept in PT Lasallefood Indonesia's 2024 Marjan Syrup advertisement entitled "Putri Hijau dan Desa Kehidupan". The advertisement successfully attracts audience attention and conveys implicit messages through its presentation. This study employs a qualitative descriptive method with a content analysis approach. The stages of analysis are conducted by describing the advertising elements, including the advertiser, message, media, target audience, and consumer response. Furthermore, the analysis uses Ferdinand de Saussure's semiotic theory to examine the implicit meanings contained in the advertisement, as well as the AIDA (Attention, Interest, Desire, Action) model to analyze its creative strategy. The results indicate that the implicit messages conveyed in the advertisement can encourage audiences to engage more deeply, both in product purchases and digital interactions. The findings also show that the use of visualization is highly effective in attracting audience attention, and that delivering messages through appealing visuals can enhance product recognition and stimulate consumer interest. In conclusion, the creative strategy implemented by PT Lasallefood Indonesia in the 2024 Marjan Syrup advertisement "Putri Hijau dan Desa Kehidupan" has been effective in fulfilling both the AIDA elements and the semiotic aspects of the advertisement